Human Security of the Indigenous Peoples in the Arctic. The Sami Case - Szpak, Agnieszka (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
For many years, indigenous peoples, their rights, culture and identity have been neglected. This depressing statement also refers to the Sami who reside in the Arctic. This paper presents the understanding of the term “indigenous peoples” and a number of their rights, including the right to selfdetermination. Their implementation is necessary for human security as they empower indigenous peoples to make decisions in matters that affect them. The author examines the concept of human security and the threats to this security in the Arctic in particular to the Sami as well as the most important provisions in international legal documents regarding the rights of indigenous peoples which include references to human security.